2015
DOI: 10.17221/8414-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal lidocaine hydrochloride for prevention of intraperitoneal adhesions following laparoscopic genitourinary tract surgery in ewes

Abstract: Adhesion formation involving the genitourinary tract is common following laparoscopic procedures. To evaluate the effectiveness of intraperitoneal lidocaine hydrochloride 1% solution for the prevention of abdominal adhesions, twenty four Santa Ines ewes submitted to laparoscopic ovum pick-up, uterine puncture and local rinsing, were randomly distributed into two groups of 12 animals, according to rinsing solution: normal saline (SG) or 1% lidocaine hydrochloride solution (LG). Laparoscopy for manipulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Ovary is prone to adhesions with the abdominal wall, omentum, and adjacent organs because of its close proximity to the abdominal cavity (MARIANO et al, 2015), and this was in the study herein. Although, these authors reported no difficulty with adhesiolysis of the ovary, they reported greater ease of adhesiolysis and possible new oocyte collection after using solutions of NaCl and 1% lidocaine, which are known to reduce adhesion formation.…”
Section: Resultsmentioning
confidence: 79%
“…Ovary is prone to adhesions with the abdominal wall, omentum, and adjacent organs because of its close proximity to the abdominal cavity (MARIANO et al, 2015), and this was in the study herein. Although, these authors reported no difficulty with adhesiolysis of the ovary, they reported greater ease of adhesiolysis and possible new oocyte collection after using solutions of NaCl and 1% lidocaine, which are known to reduce adhesion formation.…”
Section: Resultsmentioning
confidence: 79%